2020
DOI: 10.3390/cancers12051085
|View full text |Cite
|
Sign up to set email alerts
|

Ribosomal Protein S27/Metallopanstimulin-1 (RPS27) in Glioma—A New Disease Biomarker?

Abstract: Despite its significant overexpression in several malignant neoplasms, the expression of RPS27 in the central nervous system (CNS) is widely unknown. We identified the cell types expressing RPS27 in the CNS under normal and disease conditions. We acquired specimens of healthy brain (NB), adult pilocytic astrocytoma (PA) World Health Organization (WHO) grade I, anaplastic PA WHO grade III, gliomas WHO grade II/III with or without isocitrate dehydrogenase (IDH) mutation, and glioblastoma multiforme (GBM). RPS27 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 48 publications
0
27
0
Order By: Relevance
“…Our results suggest that MPS-1 plays a role in endometrioma progression, which may contribute to explore the pathogenesis of endometrioma. MPS-1 is secreted from hyperplastic tissues and can be detected in the serum [23]. MPS-1 is elevated in numerous types of cancer, including breast cancer, lung cancer, and head and neck squamous cell carcinoma [10].…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggest that MPS-1 plays a role in endometrioma progression, which may contribute to explore the pathogenesis of endometrioma. MPS-1 is secreted from hyperplastic tissues and can be detected in the serum [23]. MPS-1 is elevated in numerous types of cancer, including breast cancer, lung cancer, and head and neck squamous cell carcinoma [10].…”
Section: Discussionmentioning
confidence: 99%
“…Hegi et al, also reported that combined TMZ plus RT as compared to RT alone in the unmethylated group yielded a signi cantly prolonged PFS statistically, and combined TMZ plus RT as compared to RT alone in the unmethylated group prolonged OS, although the differences were not signi cant [8]. Furthermore, MGMT expression is heterogeneous and varies depending on the assay, and the site and timing of the assay [36,37]. Suggesting that long-term treatment with TMZ contributes to improvement of PFS and OS may thus be acceptable.…”
Section: Discussionmentioning
confidence: 99%
“…The IDH mutation status was determined by immunohistochemistry and pyrosequencing, the Ki67 status by immunohistochemistry and the MGMT promoter methylation status by high resolution melting real-time polymerase chain reaction. Since some of the specimens were already analyzed for a previous project, the methodology has been described in detail elsewhere [ 23 , 24 ].…”
Section: Methodsmentioning
confidence: 99%